Quantitative MRI evaluation of articular cartilage in patients with meniscus tear - Chen, Enqi; Hou, Wenjing; Wang, Hu; Li, Jing; Lin, Yangjing; Liu, He; Du, Mingshan; Li, Lian; Wang, Xianqi; Yang, Jing; Yang, Rui; Zhou, Changru; et al. (Frontiers in Endocrinology, 2022)
Purpose: The aim of this study was to quantitative evaluate assessment of articular cartilage volume, thickness and T2 value alterations in meniscus tear patients. The study included 32 patients with meniscus tears (17 females, 15 males; mean age: 40.16 11.85 years) and 24 healthy controls (12 females, 12 males; mean age: 36 9.14 years). All subjects were examined at 3 T MRI with 3D dual echo steady state (DESS) and T2 mapping images. All patients underwent diagnostic arthroscopy and treatment. Cartilage thickness, cartilage volume, and T2 values of 21 subregions of knee cartilage were measured by using a prototype KneeCaP software (version 2.1; Siemens Healthcare, Erlangen, Germany). Independent sample t-test were utilized to determine if there were any significant differences among subregional articular cartilage volume, thickness and T2 value between patients with meniscus tear and control group. Results: The articular cartilage T2 values in all subregions of the femur and tibia, as well as in the patella facet lateral superior in the meniscus tear group, were significantly higher (p 0.05) than in the healthy control group. The cartilage thickness of the medial femur condyle, femur trochlea, lateral femur condyle anterior and central, tibia plateau medial anterior, patella facet lateral inferior, patella facet medial inferior, and patella facet medial superior in the meniscus tear group were slightly increased in the meniscus tear group compared to the control group (p 0.05). In the femur condyle medial central, femur trochlea medial, patella facet medial inferior, tibia plateau lateral posterior, and tibia plateau lateral central, there were significant differences in relative cartilage volume percentage between the meniscus tear group and the healthy control group (p 0.05). The 19 patients confirmed by arthroscopic surgery had no cartilage abnormalities (Grade 0) in the meniscus tear group, and their T2 values in all subregions of the femur and tibia were significantly higher (p 0.05) than the healthy control group. Conclusion: The difference in articular cartilage indexes between patients with meniscus tears and healthy people can be detected by using quantitative MRI. Quantitative T2 values enable early and sensitive detection of early cartilage lesions.